Chichimene field T2 sand: a successful application of cycles in a water injection project on heavy crude oil, enabled by a novel smart selective completion system adapted for water injection - Pedro Luis Solorzano; Carlos Emilio Giosa; Carol Stephanny Rojas; Mónica Andrea Satizabal; Amelia Jhoanna Araque; Luisa Fernanda Falla; Walter Enrique Sanchez; Luis Oswaldo Castañeda; Mónica Alexandra Martínez; Diana Patricia Ahmedt (CT&F Ciencia, Tecnología & Futuro)
This paper presents the application of injection in cycles, assisted by the first smart selective completion system with remote valve operation. The completion system was installed in the Chichimene Field unit T2 (Fm. San Fernando). The results were compared with conventional water injection, technology that utilizes a simple selective completion system, in the aspects of recovery factor, water consumption, operation style, and others.